Drying temperatures affect the qualitative–quantitative variation of aromatic profiling in Anethum graveolens L. ecotypes as an industrial–medicinal–vegetable plant - Farmanpour Kalalagh, Karim; Mohebodini, Mehdi; Fattahi, Reza; Beyraghdar Kashkooli, Arman; Davarpanah Dizaj, Sanaz; Salehifar, Fatemeh; Mokhtari, Amir Mohammad (Frontiers in Plant Science, 2023)
There are several factors that affect the quality and quantity of active ingredients and essential oil (EO) content, including pre and post-harvest practices such as drying conditions. One of the most important factors in drying is temperature and then selective drying temperature (DT). In general, DT has a direct effect on the aromatic properties of Anethum graveolens. On this basis, the present study was conducted to evaluate the effects of different DTs on the aroma profile of A. graveolens ecotypes. The results showed that different DTs, ecotypes, and their interaction significantly affect EO content and composition. The highest EO yield was obtained from the Parsabad ecotype (1.86%) followed by the Ardabil ecotype (1.4%), both at 40° C. More than 60 EO compounds were identified, mainly monoterpenes and sesquiterpenes, highlighting α-Phellandrene, Germacrene D, and Dill apiole as major components in all treatments. Besides α-Phellandrene, the major EO compounds at shad drying (ShD) were β-Phellandrene and p-Cymene, while plant parts dried at 40° C showed l-Limonene and Limonene as the main constituents, and Dill apiole was detected in greater amounts in the samples dried at 60 °C. To determine the appropriate DT, simple and factorial based-ANOVA together multivariate analysis demonstrated significant differences in the compounds produced under different DTs. The results indicated that more EO compounds, mainly monoterpenes, were extracted at ShD than other DTs. On the other hand, the content and composition of sesquiterpenes increased significantly when DT was increased to 60 °C. From the genetic backgrounds point of view, the Parsabad ecotype (with 12 similar compounds) and Esfahan ecotype (with 10 similar compounds) were the most suitable ecotypes under all DTs in terms of EO compounds. Accordingly, the present study would help various industries to optimize specific DT(s) to obtain special EO compound(s) from different A. graveolens ecotypes based on commercial requirements.